2015
DOI: 10.4103/2277-9531.162386
|View full text |Cite
|
Sign up to set email alerts
|

The effect of three ergonomics interventions on body posture and musculoskeletal disorders among stuff of Isfahan Province Gas Company

Abstract: Background:Prevalence of work-related musculoskeletal disorders (WMSDs) is high among computer users. The study investigates the effect of three ergonomic interventions on the incidence of musculoskeletal disorders among the staff of Isfahan Province Gas Company, including training, sport, and installation of software.Materials and Methods:The study was performed in the summer of 2013 on 75 (52 men, 23 women) Isfahan Province Gas Company employees in three phases (phase 1: Evaluation of present situation, phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 30 publications
3
26
0
3
Order By: Relevance
“…We have been proven that a specifi c training program can reduce the pain perception in overweight forestry worker, especially in the shoulders and the lower back. These results are supported by fi ndings in other studies that indicate the positive effects of training interventions by focusing on work-specifi c requirements as well as of sedentary and moderate activities on LBP in overweight subjects (Curwin et al, 2013;Abate, 2014;Smuck et al, 2014;Habibi & Soury, 2015). Further research should investigate the effects of a training intervention regarding the amount of body fat instead of bodyweight.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…We have been proven that a specifi c training program can reduce the pain perception in overweight forestry worker, especially in the shoulders and the lower back. These results are supported by fi ndings in other studies that indicate the positive effects of training interventions by focusing on work-specifi c requirements as well as of sedentary and moderate activities on LBP in overweight subjects (Curwin et al, 2013;Abate, 2014;Smuck et al, 2014;Habibi & Soury, 2015). Further research should investigate the effects of a training intervention regarding the amount of body fat instead of bodyweight.…”
Section: Discussionsupporting
confidence: 70%
“…Other existing studies also show positive training effects on musculoskeletal pain especially in overweight subjects (Abate, 2014). That means the results from the overweight sample confi rm the existing positive effects of training interventions based on work-specifi c requirements (Curwin et al, 2013;Habibi & Soury, 2015). No differences can be found comparing the normal weight IG to the normal weight CG.…”
Section: Discussionsupporting
confidence: 55%
“…A number of effects of PE have been reported, including decreased musculoskeletal symptoms and industrial accidents, reduced work injury-related expenditure, and fewer days of absence 6,[10][11][12][13][14][15][16] . However, the results of randomized controlled trials (RCTs) have shown no effect on the prevalence of low back pain or neck pain 17) ,n od ecrease in pain intensity 18) , and no prophylactic effects on musculoskeletal disorders 19,20) .…”
Section: Introductionmentioning
confidence: 99%
“…Some of the problems associated with occupational health are workload. The method used to determine the amount of workload, one of them by calculating the pulse of work with the method of 10 pulses, while the measurement of resting pulse rate method 15 seconds [7]. Carrivick et.al.…”
Section: Introductionmentioning
confidence: 99%